ISOLATION AND PROPERTIES OF A SURFACE ANTIGEN OF STAPHYLOCOCCUS AUREUS - Morse, Stephen I. (The Rockefeller University Press, 1962)
A technique is described for the isolation and purification of an antigen released into the culture medium by Staphylococcus aureus strain Smith. The antigen was found to be homogeneous when examined by free electrophoresis and analytic ultracentrifugation. Immunologic homogeneity was established by immunoelectrophoresis and quantitative precipitin tests using high titer antiserum prepared against the homologous organism. Chemical analysis showed that the antigen contained 70 per cent carbohydrate, of which approximately 30 to 35 per cent was believed to be glucosamine. The analytic data suggested that another amino sugar, probably carboxylated, was also present, but extreme lability of this compound to mild hydrolytic procedures has thus far precluded further identification. The remainder of the antigen was composed of alanine, glutamic acid, aspartic acid, lysine, glycine, serine, and threonine. No muramic acid was found. The chemical and physical data indicate that the antigen described herein is a previously unrecognized component of Staphylococcus aureus. The purified compound was capable of absorbing agglutinating antibody from antiserum prepared against S. aureus Smith, indicating that it was a surface component of this encapsulated staphylococcus. It is proposed that the antigen be known as the Smith surface antigen (SSA). The injection of SSA into rabbits did not produce precipitating antibodies. However, SSA did precipitate at low concentrations (0.5 µg/ml) with antiserum prepared against S. aureus Smith and one other strain of S. aureus tested. Antiserum against two other aureus strains reacted only with high concentrations of SSA. SSA did not react with S. albus antiserum or with normal sera from several animal species. Experiments are in progress to define further the distribution of SSA. Intradermal injection of small quantities of SSA into rabbits immunized with S. aureus Smith evoked a reaction of cutaneous hypersensitivity, which was maximal in 8 to 12 hours. SSA appeared to be the substance responsible for the ability of S. aureus Smith to resist engulfment by phagocytes, since absorption of Smith antiserum with SSA effectively removed opsonizing antibodies. SSA induced protection in mice against experimental staphylococcal disease. The subcutaneous injection of 0.1 µg resulted in protection against a subsequent intraperitoneal challenge with 50 to 100 LD(50)'s of S. aureus Smith suspended in mucin. Increasing as well as decreasing the immunizing dose resulted in significantly less protection.